DEVELOPING AND RECOGNIZING SKILLS, TRANSFERABLE SKILLS, PERSONAL AND ACADEMIC SKILLS - Bahadirovna Mirkasimova, Madina; Shaxnoza Farxod qizi, Ibodullayeva (Scientific Impulse, 2023)
Transferable skills are universally essential for every branch. They contribute to success and the victory of a group, client, or organization. They are important in studying, job and other branches that any personnel comes across in their lifestyle. In addition to this, they permit to control over a career way and guarantee a advancement in career change. In a way, these are abilities that never go out of style. Transferable skills will take after and back your victory professionally, so long as you contribute and put deliberateness exertion into sharpening them. This article highlights key transferable skills that have been transferred and/or developed to the workplace from previous school, collage, lyceum and higher education experience. In the work results of survey that are taken from graduate students are discussed. The students consider communication, time management, organization, responsibility and problem solving as the most transferable skills. While, diligence, focusing, leadership, initiative are secondary ones.